How economic instruments address sustainable nutrient use: the example of phosphorus governance - Beatrice Garske; Katharine Heyl; Felix Ekardt (Environmental Sciences Europe)
Abstract Background The widely inefficient agricultural use of phosphorus (P) causes environmental damage. At the same time, an uneven resource distribution risks supply shortages for this essential nutritional element. Effective governance solutions help to stimulate a more sustainable P management and fulfil the human right to food. This article applies a qualitative governance analysis to develop an integrated governance solution for the multi-layered problems of agricultural P use primarily by economic instruments. Based on P-related challenges and the cornerstones of sustainable P management, an assessment scheme for economic instruments for P is conceptualized and applied. Results Results show that there is no ‘one fits all’ solution for all problems associated with agricultural P use. We find a combination of (1) an economic instrument for rock phosphate-based fertilizers with (2) a tax for P surpluses and (3) a regulation on contaminant levels in fertilizers addresses all P-related problems effectively. Conclusions The optimal P governance combines economic and regulatory policy instruments. Besides addressing sustainable P management and thus contributing to the implementation of the right to food, the policy mix also positively impacts further ecological challenges such as disrupted N cycles, climate change and biodiversity loss.